Strategies to improve environmental networks for pollution control: Evidence from eco-compensation programs in China. (15th March 2019) - Wang, Xiaohu; Berman, Evan M.; Chen, Don-yun; Niu, Xuejiao
Abstract: Networks are increasingly popular in dealing with dynamic and complex environmental policy issues, including pollution control and abatement, which require solutions for collaborative and innovative actions involving multiple institutions or entities. Effective network implementation produces better environmental policy outcomes, but little is known about how to improve network implementation. Framed in the network implementation capacity-building approach, this study examines what strategies are adopted by network administrators to improve implementation, and how these strategies work. Evidence from two environmental financing networks in China shows that strategies designed to mobilize resources and maintain network long-term stability improve network implementation. We call for a research agenda that emphasizes network implementation capacity-building in emerging economies where collaborative activities are desired to pool resources and expertise in face of resource shortage and daunting environmental challenges. Highlights: Networks are increasingly popular in environmental governance of emerging economies. Success of network implementation depends on strategies adopted by network management. The strategy designed to mobilize resources improves network implementation. The strategy designed to maintain long-term stability improves network implementation. Network capacity building is a key in improving network implementation.